The effect of corporate governance on company value (Empirical study of LQ 45 companies listed on the Indonesia Stock Exchange period 2015-2017) - Karmila Febrianti; Nurul Hasanah Uswati Dewi (The Indonesian Accounting Review, 2019)
This research aims to examine the effect of corporate governance on company value of LQ 45 companies listed on the Indonesia Stock Exchange (IDX). The corporate governance mechanism consists of institutional ownership, proportion of independent commissioner, managerial ownership, independent audit committee, remuneration and nomination committee, board of directors, and board of commissioners, while firm value is proxied by Tobin’s Q. This research used 106 companies as a sample taken from a population of 135 companies in LQ 45 listed on the Indonesia Stock Exchange (IDX) period 2015-2017. The data were analyzed using a multiple linier regression analysis with SPSS program. The result shows that corporate governance mechanisms which are proxied by institutional ownership, proportion of independent commissioners, board of directors, and board of commissioners have an effect on firm value, while the corporate governance which are proxied by managerial ownership, independent audit committee, and remuneration and nomination committee have no effect on firm value.